O bohatýrském bytování Múz: Xavier Galmiche: Znaky a přízraky - Catherine Ébert-Zeminová (Svět Literatury, 2025)
Xavier Galmiche’s book Znaky a přízraky: Výbor ze statí o české a středoevropské literatuře (Signs and Spectres: Selected Essays on Czech and Central European Literature) brings together some forty pa pers written between 2000–2022 mostly in French. In the geographical context indicated by the title, the Galmiche embraces a long period from the 19th to the 21st century, often extending the field into fine arts, history of ideas, and culture. The review article argues that the unifying thread of Galmi che’s works lies in his interest in borders: linguistic, ethnical, national or even political. He demonstrates how the multiple borders and the mixture of criteria which determine them foster the individual poetics or various aesthetic phenomena on larger scales, both synchronic and diachronic. A remarkable quality which the analysis of Galmiche’s contributions points out consists mainly in the author’s independence from fashionable methodological trends, and particularly the fact that it values and respects the rigorously historical and philological anchorage of the critical approach to literary texts.